1977
DOI: 10.1113/jphysiol.1977.sp011960
|View full text |Cite
|
Sign up to set email alerts
|

The influence of food intake and ambient temperature on the rate of thyroxine utilization.

Abstract: SUMMARYYoung growing pigs of both sexes were subjected to changes in (1) energy intake, (2) ambient temperature, and (3) bulk of food. The rate of disappearance of injected 125I-labelled thyroxine from the plasma (K) was measured. An analysis of variance revealed that the effect attributable to changes in the energy content of the food intake was statistically significant (P < 0.01). A change in ambient temperature had no statistically significant effect on K, nor did a change in the bulk of food when energy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
3
6
0
Order By: Relevance
“…Meals containing moderate amounts of carbohydrates (diets A and B) were associated with increases in serum T4 concentrations during the first several hours after meal completion. These observations are consistent with reports that T4 secretion rates and serum T4 concentrations are in¬ creased after the ingestion of meals containing carbo¬ hydrate by pigs (Ingram & Kaciuba-Uscilko, 1977;Ingram & Evans, 1980;Dauncey, Ingram, Macari & Ramsden, 1982), man (Spaulding, Chopra, Sherwin & Lyall, 1976;Danforth, Horton, O'Connell et al 1979) and cattle (Blum, Gingins, Schnyder et al 1979 ;Blum, Thomson & Bickel, 1979e). In addition, thyro¬ trophin (TSH) secretion has been reported to increase after feeding in rats (Hugues, Burger, Grouselle et al 1983) and man (Hugues, Burger, Pekary & Hershman, 1984).…”
Section: Discussionsupporting
confidence: 92%
“…Meals containing moderate amounts of carbohydrates (diets A and B) were associated with increases in serum T4 concentrations during the first several hours after meal completion. These observations are consistent with reports that T4 secretion rates and serum T4 concentrations are in¬ creased after the ingestion of meals containing carbo¬ hydrate by pigs (Ingram & Kaciuba-Uscilko, 1977;Ingram & Evans, 1980;Dauncey, Ingram, Macari & Ramsden, 1982), man (Spaulding, Chopra, Sherwin & Lyall, 1976;Danforth, Horton, O'Connell et al 1979) and cattle (Blum, Gingins, Schnyder et al 1979 ;Blum, Thomson & Bickel, 1979e). In addition, thyro¬ trophin (TSH) secretion has been reported to increase after feeding in rats (Hugues, Burger, Grouselle et al 1983) and man (Hugues, Burger, Pekary & Hershman, 1984).…”
Section: Discussionsupporting
confidence: 92%
“…The changes seen in the disappearance rate of reverse T3 follow a similar trend to that reported earlier for (Ingram & Kaciuba-Uscilko, 1977), although the rate of disappearance of T4 was more sensitive, since a reduction in food intake from 4% to 2% induced a fall in clearance rate from plasma. This may be because the longer plasma half-life of T4 compared with that of reverse T3 makes any change more easily detectable.…”
Section: Resultssupporting
confidence: 78%
“…Labelled T3 and reverse T3 each in a dose of 25 µ were injected via the catheter and washed in by withdrawing and reinjecting blood several times before finally injecting 5 ml 0-9% NaCl solution. This procedure has previously been proved to be satisfactory (Ingram & Kaciuba-Uscilko, 1977). Subsequently 5 ml samples of blood were withdrawn at intervals into heparinized tubes and the plasma separated.…”
Section: Cathetersmentioning
confidence: 99%
“…Although Ingram and Evans (1980) reported no effect of meal consumption on T4 concentrations in young pigs after a 12-h fast, they concluded that any changes in T4 secretion or utilization rates will be highly dependent on the sizes and caloric densities of the meals. Evans and Ingram (1977), Ingram and Kaciuba-Uscilko (1977), Ingram and Evans (1980) and Blum et al, (1980) reported increases in T4 secretion rates in growing pigs after increases in the amount and energy content of meals. Danforth et al (1979) reported a similar finding in humans.…”
Section: Discussionmentioning
confidence: 96%